Bilateral Femoral Neck Fracture in a Postpartum Woman: Beware of the Risk Factors - Ismail Sahan; Julie De Deken; Konstantinos Anagnostakos (Case Reports in Orthopedics)
Bilateral femoral neck fractures pose a rare injury. Literature data describe this entity in association with epileptic seizures, renal osteodystrophy, electric shock, pregnancy-associated transient osteoporosis, and hypocalcemic seizure. In the present work, we report on a rare case of a 28-year-old woman who suffered from such an injury 3 days postpartum. The patient had two predisposing factors (epilepsy history, transient osteoporosis) that were neglected as possible risk factors by the treating physicians. Awareness of the factors might have prevented the emergence of this injury.